Mechanism and Stability Analysis of Deformation Failure of a Slope - Yingfa Lu; Gan Liu; Kai Cui; Jie Zheng (Advances in Civil Engineering, 2021)
Force distribution during progressive slope failure is an important element in slope stability analysis. In this study, five mechanical failure modes are proposed for thrust- and pull-type slopes, respectively, and five field forms of thrust-type slopes are described. The properties of progressive failure are evaluated quantitatively: the failure mode of slope obeys the geo-material rule under the peak stress state, and the instability range is gradually developed. The critical stress state zone is in the process of dynamic change with the development of deformation. It appears that the driving sliding force is greater than the frictional resistance along the sliding surface. When rock or soil stabilizing stresses are at maximum, the vector sum of the driving sliding stress and stabilizing stress is equal to zero at the critical state. The frictional resistance is equal to the driving sliding force in the stable and less-stable regions, and the normal pressure is wherever equal to the counterpressure. Rigid, flexible, and rigid-flexible design theories are proposed for slope control. New terms are defined and used to evaluate the stability. The conventional local and surplus stability factors of slopes and their calculation are explained. The force distribution rule is analyzed during progressive failure, and the conventional stability factor definition is discussed. The geological settings and monitoring data of landslides are used to analyse changes in the critical stress state. An example is given to illustrate the failure process analysis. The results show that progressive failure can be well represented and the safety factor can be well described by the main thrust method (MTM), comprehensive displacement method (CDM), and surplus displacement method (SDM), which can be used to feasibly evaluate slope stability.